Moderating Effects of Dark Triad on the Relationships of Mobbing and Abusive Supervision with Outcomes - Elif Bingül; Aslı Göncü-Köse (Journal of Work and Organizational Psychology, 2024)

(untitled)
The Dark Triad (DT) personality traits (i.e., Machiavellianism, narcissism, and psychopathy) are among the antecedents of workplace mistreatment (WM). However, we have limited knowledge regarding how the DT traits of victims affect their responses to WM. We investigated the moderating effects of the DT in the links of mobbing and abusive supervision with job satisfaction, organizational citizenship behaviors (OCBs), and counterproductive work behaviors (CWBs). Data were collected from 715 working adults. Employees who scored high on narcissism were more likely to have higher scores on CWBs than those who scored low on narcissism in case of mobbing and abusive supervision. Individuals who scored high on psychopathy reported higher levels of job satisfaction under high mistreatment conditions than those who scored low on psychopathy. Individuals who scored high on Machiavellianism reported higher levels of OCBs and lower levels of CWBs under high mistreatment than those who scored low on Machiavellianism.